RUMORS AS A SOURCE FOR THE STUDY OF WOMEN’S EVERYDAY LIFE IN THE URBAN SPACE OF KABARDINO-BALKARIA - Konovalov, Andrej Anatol'evic; Bitokova, Tamara Vladimirovna; Tekueva, Madina Anatol'evna (History, Archeology and Ethnography of the Caucasus, 2022)
The present paper attempts to study a number of sources that examine the daily life in a Soviet and post-Soviet provincial town, in particular its female population, from a new perspective; to turn to events that have not been previously the subject of consideration in the Caucasian studies. The approach used in the history of everyday life makes it possible to identify the quality of life that developed during the Soviet era (the culminating period of which in the context of this article is the Khrushchev Thaw), which subsequently acquired a stable character. It is shown that the ordinary life of women was transformed by the socio-economic and political reconstruction of society. Using these examples of the normal course of life within the transitional periods, it becomes possible to approach the study of the everyday living conditions of the citizens of the republic. The paper focuses its attention on the less popular form of oral sources – rumors. Several rumors of the 1960s and two stories from the preceding and subsequent periods reflect the spirit of the times. Their analysis shows how in the peaceful course of everyday life, in the depths of women’s consciousness, emotions mature, seizing the masses.